Association of G71R Mutation of the UGT1A1 Gen with Neonatal Hyper Bilirubinemia in the Iranian Population - Ebrahim Dastgerdy; Gholamali Mamori; Jalil Afshari; Reza Saeedi; Fatemeh Shahbazi; Mahboobeh Shirazi (Tehran University of Medical Sciences, 2012)
Objective: Jaundice with indirect hyperbilirubinemia is one of the most common neonatal problems that occur in 60% of term and 80% of preterm neonates but the causes are mostly unknown. It is suggested that race plays an important role in the prevalence of hyperbilirubinemia. It is a common problem in Iran that worries both parents and pediatricians. It has been found that a mutation in the UGT1A1 gene is responsible for structural changes in an encoded enzyme which reduces the function of the enzyme. Materials and methods: This is a case-control study carried out in Ghaem Educational Hospital, Mashhad University of Medical Sciences from December 2007 for the period of one year. 26 healthy neonates tested for indirect hyperbilirubinemia within first week after full-term delivery and 53 healthy neonates without hyperbilirubinemia as a control group were included. Genomic DNA extracted using 2 cc blood sample followed by RFLP-PCR for detection of G71R mutation of UGT1A1 gene have been performed. SPSS software (version 16), t- test and chi square analysis have been used for statistical analysis of obtained data. Results: 4.3% of the hyperbilirubinemic group was homozygotes for mutation in UGT1A1 and 26.1% were heterozygotes while 69.6% had no mutation. 21.3% of the control group had the mutation with 4.3% being homozygote and 17% being heterozygote. Conclusion: Frequency of G71R mutation in the hyperbilirubinemia group was not significantly more than that in the control group among Iranian newborns. This finding suggests that G71R mutation may not contribute to the development of neonatal hyperbilirubinemia in Iranian newborns. It is recommended to establish further studies using well-designed inclusion criteria and more specialized mutation analysis techniques which cover all types of probable mutations in G71R gene.